2014
DOI: 10.7567/jjap.53.034101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrathin AlN spacer on electronic properties of GaN/SiC heterojunction bipolar transistors

Abstract: GaN/SiC heterojunction bipolar transistors (HBTs) with an ultrathin AlN spacer layer at the n-GaN/p-SiC emitter junction are proposed for the control of the electronic properties of GaN/SiC heterojunctions. The insertion of an AlN spacer is found to be promising in terms of improving electron injection efficiency owing to the reduced potential barrier (0.54 eV) to electron injection and reduced recombination via interface traps. We also investigated the effect of pre-irradiation of active nitrogen atoms (N*) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…We observed that the turn-on voltage ( 0.75 V) was smaller compared with the flatband voltage ( 1.2 V) and the magnitude of the current increased for larger reverse bias voltage for respective curves. Similar result was observed in the p-GaAs/n-GaN (11) and p-SiC/n-GaN (12) junctions fabricated by wafer fusion and molecular beam epitaxy, respectively, which was attributed to the scheme of interface states assisted tunneling. The interface states should be formed at the boding interface of the p + -GaAs/n-SiC heterojunction and distributed in the amorphous layer of the bonded interface, which is due to damages fabricated during the Ar plasma irradiation in the SAB process according to our previous report.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that the turn-on voltage ( 0.75 V) was smaller compared with the flatband voltage ( 1.2 V) and the magnitude of the current increased for larger reverse bias voltage for respective curves. Similar result was observed in the p-GaAs/n-GaN (11) and p-SiC/n-GaN (12) junctions fabricated by wafer fusion and molecular beam epitaxy, respectively, which was attributed to the scheme of interface states assisted tunneling. The interface states should be formed at the boding interface of the p + -GaAs/n-SiC heterojunction and distributed in the amorphous layer of the bonded interface, which is due to damages fabricated during the Ar plasma irradiation in the SAB process according to our previous report.…”
Section: Discussionsupporting
confidence: 80%
“…Maximum common-base current gains of 0.01 and 0.03 were obtained on GaN/4H-SiC HBTs and GaN/6H-SiC HBTs, respectively, with a base doping concentration of 1 Â 10 18 cm À3 . Continuous work to achieve a high emitter injection efficiency, e.g., by the utilization of an AlN spacer layer with a smaller lattice mismatch with SiC 22) and the band offset control of the GaN/SiC heterojunction with an AlGaN emitter, 23,24) will be presented in the future.…”
Section: Discussionmentioning
confidence: 99%